PEMANFAATAN HASIL PENGEMBANGAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR SISWA DI SMAN 1 BUNGO - rohmawati, yuli (Jurnal Tunas Pendidikan, 2022)
This research is a research and development (Research and Development) in collaboration with Classroom Action Research (CAR) which aims to increase student interest and achievement through the use of learning media. The development model used by ADDIE is continued with the CAR stages, namely planning, implementation, observation and reflection. This research was conducted at SMAN 1 Bungo, with the subject of class X MIPA 2 students in the even semester of the 2019/2020 school year. The data was obtained from the results of material and media expert validation, interest questionnaires and student knowledge test results. The results of the validation of the media feasibility test obtained an average score of 3.27 with a very feasible category. Based on the results of observations of student interest there was an increase before and after using the media by 12.25%. Based on the results of the post test in the pre-cycle, the average student score was 74.75%, in the first cycle it was 75% and 79.68% in the second cycle. Based on completeness, the number of students who met the KKM in the first cycle was 62% and increased in the second cycle by 81%. These results indicate that the indicators of success are fulfilled, that 75% of students have completed. So it can be concluded that the application of video-based economic learning media can improve student achievement in class X MIPA 2 SMAN 1 Bungo.